2000
DOI: 10.1037/0022-3514.79.6.1007
|View full text |Cite
|
Sign up to set email alerts
|

The age of anxiety? The birth cohort change in anxiety and neuroticism, 1952–1993.

Abstract: Two meta-analyses find that Americans have shifted toward substantially higher levels of anxiety and neuroticism during recent decades. Both college student (adult) and child samples increased almost a full standard deviation in anxiety between 1952 and 1993 (explaining about 20% of the variance in the trait). The average American child in the 1980s reported more anxiety than child psychiatric patients in the 1950s. Correlations with social indices (e.g., divorce rates, crime rates) suggest that decreases in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
564
10
32

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 598 publications
(636 citation statements)
references
References 85 publications
30
564
10
32
Order By: Relevance
“…Time-lag studies of the Big Five are far rarer than cross-sectional and longitudinal studies; two important recent meta-analyses offer a comparison source for Neuroticism (Twenge, 2000) and Extraversion (Twenge, 2001). These studies examined how, across studies, publication year correlated with sample means for anxiety and Extraversion.…”
Section: Addressing Sampling and Cohort Concernsmentioning
confidence: 99%
“…Time-lag studies of the Big Five are far rarer than cross-sectional and longitudinal studies; two important recent meta-analyses offer a comparison source for Neuroticism (Twenge, 2000) and Extraversion (Twenge, 2001). These studies examined how, across studies, publication year correlated with sample means for anxiety and Extraversion.…”
Section: Addressing Sampling and Cohort Concernsmentioning
confidence: 99%
“…In two meta-analyses, Twenge (2000) found that Americans' neuroticism and anxiety scores have increased by almost 1 full standard deviation in recent decades. When correlating this increase with a number of societal indicators, she found that decreases in social connectedness (e.g., increase in divorce rates and the percentage of people living alone) may be the driving factor.…”
Section: Study 2: International Levelmentioning
confidence: 99%
“…These disorders are associated with low self-esteem, poor problem solving skills, social inhibition, and a strong desire to be accepted (Anderson, Williams, McGee, & Silva, 1987;Khalid-Khan, Santibanez, McMicken, & Rynn, 2007;McGee et al, 1990;Twenge, 2000). Altogether these characteristics may predispose adolescents with anxiety disorders to experience unique stressors while using Facebook.…”
Section: Introductionmentioning
confidence: 99%